The associations of circulating microRNA-133a with parameters of hypertension heart disease in patients with arterial hypertension and obesity. (25th November 2020) - Yushko, K; Koval, S; Snihurska, I; Mysnychenko, O
Abstract: Introduction: Blood pressure (BP) elevation leads to chronical increasing left ventricular (LV) overload, LV hypertrophy (LVH), impaired LV relaxation, development of LV diastolic dysfunction (DD), left atrial (LA) enlargement, which result in development of hypertension heart disease (HDD), increased risk of atrial fibrillation and heart failure. MicroRNA-133a is one the epigenetics factor, which has cardioprotective properties, but its role in the development of HHD in hypertension patients with obesity is not well understood. Purpose: The aim of the study was to investigate the circulating microRNA-133a levels in patients with hypertension and obesity and to define its associations with components of HHD. Methods: The study involved 82 patients with arterial hypertension grades 2–3 and obesity (44 men and 38 women) aged 43 to 70. All patients were separate in two groups: 45 patients with HHD (main group) and 37 patients without HHD (comparison group). The control group consisted of 21 practically healthy individuals of comparable gender and age. The HHD was defined as LVH in hypertension patients with/without LV DD. The LVH was determined according to the 2018 ESC/ESH guidelines. The LV DD was determined according to the 2016 ASE/EACVI recommendations. Obesity was diagnosed at body mass index ≥30 kg/m 2 . Circulating plasma microRNA-133a levels were obtained by polymerase chain reaction using the CFX96 Touch System, "TaqMan microRNA Assay" and "TaqMan® Universal PCR Master Mix" reagent kits. Results: The levels of microRNA-133a in main group were significantly lower than in comparison group and control group (0.133 [0.099; 0.184] vs 0.238 [0.155; 0.410], p<0.05 and 0.382 [0.198; 0.474]), p<0.05). In the main group 23 patients had LV DD and 25 patients had normal LV diastolic function. In patients with LV DD the levels of circulating plasma microRNA-133a were significantly lower than in patients with normal LV diastolic function (0.094 [0.067; 0.147] vs 0.152 [0.092; 0.189]), p<0.05). In the main group there was a statistically significant negative correlation between microRNA-133a levels and LV mass index (R=−0.37, p<0.01) and no significant correlation with ejection fraction, LA size or E/e' (averaged) ratio (p>0.05). In patients of the comparison group there were not significant associations of microRNA-133a levels with LV parameters (p>0.05). Conclusion: The results of the study indicate a significant role of decreased circulating plasma microRNA-133a levels in patients with arterial hypertension and obesity in the pathogenesis and development of HHD and such its components as LVH and LV DD. Funding Acknowledgement: Type of funding source: None